Budaya W2019 - Chan, Margaret (UiTM Sarawak, 2020)
Associate Professor Dr. Margaret Chan was invited as one of the speakers in BUDAYA W2019-Colloquim in conjunction with the 2nd BIMP-EAGA Budayaw Festival 2019 held on the 20-22 November 2019. BIMP-EAGA stands for Brunei, Indonesia, Malaysia, Philippines East Asean. The festival was celebration of arts and culture, which was held from 19-23 November 2019 in Kuching, Sarawak with the themes ‘Beauty in Cultural Diversity' showing the solidarity among people from member-countries all different in culture, yet identical in tradition